Behavioral Intention Toward Online Food Delivery (OFD) Services (the study of consumer behavior during pandemic Covid-19) - Dian Novita; Nurul Husna; Ahmad Azwari; Agung Gunawan; Destiana Trianti; Cintya Bella (Universitas Islam Bandung, 2020)
Pandemic Covid-19 , social distancing and sel- quarantine has a great impact to consumer behavioral, most of the activities move to online activities, consumer prefer online transaction to ensure they are safety. The purpose of this research is to analyze correlation between convenience motivation and behavioral intention during pandemic in the last few months (since government announce a big social distancing in Indonesia in March, 2020). This research using purposive sampling technique in which only those who are using online food delivery services during pandemic that can be the respondent, the questionnaire spread out among 209 respondents. There are 4 variables in this research they are: time saving orientation (TSO), prior online purchase experience (POPE), convenience motivation (CM) and behavioral intention towards OFD services (BI) they are analyzed with path analysis model, using warpPls 7.0. this research revealed that there is positive relationship between convenience motivation and behavioral intention toward OFD services.